The Implication of the Polymorphisms of COX-1, UGT1A6, and CYP2C9 among Cardiovascular Disease (CVD) Patients Treated with Aspirin - Nur Jalinna Abdul Jalil; Zakaria Bannur; A. Derahman; O. Maskon; Noor Darinah; Hamat Hamidi; Osama Ali Gunasekaran; Mohd Rafizi; Nur Izatul Azreen; Teh Lay Kek; Mohd. Zaki Salleh (Frontiers Media S.A., 2015)
PURPOSE:  Enzymes potentially responsible for the pharmacokinetic variations of aspirin include cyclooxygenase-1 (COX-1), UDP-glucuronosyltransferase (UGT1A6) and P450 (CYP) (CYP2C9). We therefore aimed to determine the types and frequencies of variants of COX-1 (A-842G), UGT1A6 (UGT1A6*2; A541G and UGT1A6*3; A522C) and CYP2C9 (CYP2C9*3; A1075C) in the three major ethnic groups in Malaysia. In addition, the role of these polymorphisms on aspirin-induced gastritis among the patients was investigated. METHODS: A total of 165 patients with cardiovascular disease who were treated with 75-150 mg daily dose of aspirin and 300 healthy volunteers were recruited. DNA was extracted from the blood samples and genotyped for COX-1 (A-842G), UGT1A6 (UGT1A6*2 and UGT1A6*3) and CYP2C9 (CYP2C9*3; A1075C) using allele specific polymerase chain reaction (AS-PCR). RESULTS: Variants UGT1A6*2,*3 and CYP2C9*3 were detected in relatively high percentage of 22.83%, 30.0% and 6.50%, respectively; while COX-1 (A-842G) was absent. The genotype frequencies for UGT1A6*2 and *3 were significantly different between Indians and Malays or Chinese. The level of bilirubin among patients with different genotypes of UGT1A6 was significantly different (p-value < 0.05). In addition, CYP2C9*3 was found to be associated with gastritis with an odd ratio of 6.8 (95 % Cl OR: 1.39 - 33.19; P = 0.033). CONCLUSION: Screening of patients with defective genetic variants of UGT1A6 and CYP2C9*3 helps in identifying patients at risk of aspirin induced gastritis. However, a randomised clinical study of bigger sample size would be needed before it is translated to clinical use.